Tratamentos químico e biológico para melhorar a qualidade de volumosos para ruminantes - SILVA, Ivone Rodrigues da (2017)
The objective of this study was to evaluate the nutritive value of the hay of the cassava stalk with urea and sugar cane silage inoculated with bacterial additives. To the A randomized complete design with five treatments (urea levels 0, 2, 4, 6 and 8% of dry matter, DM) and five replicates (bags for chemical treatment) was used. In the evaluation of sugarcane silage, the design was completely randomized in a factorial arrangement 3 x 3 (fermentation periods 10, 60 and 90 days x addition of inoculant Propionibacterium acidipropionici or Lactobacillus buchnerie not inoculated). The content of DM, crude protein (PB), neutral detergent fiber (NDF), acid detergent fiber (FDA), neutral detergent insoluble nitrogen (NIDN), hemicellulose (HEM), lignin, ashes; And ruminal degradability, regarding ruminal degradation parameters a, b and c, potential degradation and effective degradability of DM. Cassava stem hay presented lower DM content and higher CP content at the 8% level of urea. The levels of NIDN, NDF, FDA and lignin decreased as the level of urea in the material was increased. For the degradation parameters, the water soluble fraction (a) increased from the 4% level of urea and fraction b presented higher values ​​for levels 4, 6 and 8% of urea. Potential degradation (A) was higher at the 4% level of urea, the effective degradability at the rates of 2, 5 and 8% / hour, was higher than the 6% level of urea. For the sugarcane silage, the period of 90 days presented a lower pH mean, between the fermentation periods, only in the silage without additive there was a reduction in the dry matter content with a period of 90 days. The CP content was not influenced (P> 0.05) by the fermentation period and microbial additive. The bacterium P. acidipropionici provided a lower NDF content in the period of 10 days. There was no difference (P> 0.05) for the contents of HEM and FDA and lignin. The silages with the bacterium P. acidipropionici presented higher soluble fraction, potential degradation and effective degradability at 10 days of fermentation, at 60 days there was no variation in the soluble fraction, but the control silage presented higher insoluble fraction, greater potential degradation and effective degradability. At 90 days of fermentation, the silages with L. buchneri presented higher fraction a, rate of degradation and DE, the control treatment obtained higher value of b. Cassava stem hay ammoniation improves the chemical composition and is recommended at 6 to 8% urea level in DM. However, it presented low levels of ruminal degradation. The inoculants were efficient in maintaining the DM contents of the silages, however, they did not alter the degradation.